Pattern transformation of thermo-responsive shape memory polymer periodic cellular structures. (1st October 2015) - He, Yuhao; Guo, Siusiu; Liu, Zishun; Liew, K.M.
Abstract: In this paper, pattern transformation behaviors of shape memory polymer (SMP) periodic cellular structures are investigated through numerical simulations. In order to describe SMP cellular structures behavior in the shape memory cycle, generalized thermo-mechanical viscoelasticity theory coupling time–temperature effect are utilized with the generalized Maxwell model and the Williams–Landel–Ferry (WLF) equation. Similar to other normal periodic cellular structures, SMP periodic cellular structures also display the interesting phenomenon of novel pattern transformation when the structures are loaded by compression force beyond a critical value. Different from other periodic cellular materials, novel transformed pattern for SMP material can be fixed via cooling to a temperature below the glass transition temperature Tg, and this fixed pattern can further be recovered to its original pattern by reheating to a temperature above Tg . Moreover, viscous property of SMP during shape memory cycle is taken into account by considering the effects of nominal strain rate and temperature on the pattern transformation. Time–temperature superposition principle is adopted to explain these effects. On the other hand, this transformation phenomenon for SMP can be triggered even by the stress relaxation process. It is also observed that the auxetic behavior (negative Poisson ratio) exists in the pattern transformation during both the compression process and the stress relaxation process for SMP periodic cellular structures. With present study, we are able to gain deeper insights and explain some of the new interesting physical phenomena observed in reported experiments for SMP periodic cellular structures. Besides, these new findings can be used to design appropriate SMP structures in special applications.